Wanprestasi Perjanjian Kerja Waktu Tertentu Akibat Pandemi Covid-19: Default of a Specific Time Work Agreement Due to the Covid-19 Pandemic - Fatma Meria; Serlika Aprita; Heni Marlina (DOKTRINA: JOURNAL OF LAW, 2022)
The purpose of this study will be to discuss the cancellation of a certain time work agreement due to covid-19 in terms of Law no. 13 of 2003 concerning Manpower and the legal consequences of canceling a certain time work agreement due to the covid-19 pandemic. The research method uses normative juridical research, where this type of research discusses doctrines or principles in legal science aimed at written regulations. The results showed that the cancellation of a certain time agreement as a result of the Covid-19 pandemic, including for reasons of termination of employment, seen from Law no. 13 of 2003 concerning Manpower Article 1 number (25) “Termination of employment is the termination of employment relations due to a certain matter which results in the termination of rights and obligations between workers or workers and employers. The reasons for termination of employment during the pandemic are of course various, but it cannot be denied that many entrepreneurs interpret the Covid-19 outbreak as a natural disaster as a force majeure reason for terminating workers to reduce losses due to the Covid-19 pandemic. 19. The legal consequences of canceling work agreements for a certain time during the Covid-19 pandemic, namely termination of employment by employers during the Covid-19 pandemic. The Covid-19 pandemic is used as an excuse for Force Majeure for employers to terminate employment. Force Majeure can legally be used as an excuse by business actors to lay off their workers, as has been explained in Article 164 Paragraph (1) of Law no. 13 of 2003 concerning Manpower.